1999
DOI: 10.1046/j.1365-2788.1999.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Family factors influencing out‐of‐home placement decisions

Abstract: Flying in the face of national community care policies, families of young children with severe disabilities continue to seek out-of-home placement The present paper explores the factors which influence families to care for their children at home or to place them out-of-home. Data for the present study were derived from a qualitative in-depth study of the everyday family life experiences of 167 families of young children with a disability and high support needs. One hundred and twenty-five (75%) of these famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 11 publications
1
55
1
Order By: Relevance
“…The most common reasons for failure of home care are the lack of community and family resources, lack of financial resources, and emotional depletion of the family. 22 For simplicity, an approach to caring for children with complex, chronic conditions at home can be divided into 7 main areas: (1) defining the basic medical issues; (2) defining the developmental issues; (3) understanding the underlying diagnoses; (4) the role of the PCP and the medical home; (5) the needs of the family; (6) the ongoing home care agencies and services required; and (7) assessment of the community and educational services.…”
Section: Insurance Coverage For Care At Homementioning
confidence: 99%
“…The most common reasons for failure of home care are the lack of community and family resources, lack of financial resources, and emotional depletion of the family. 22 For simplicity, an approach to caring for children with complex, chronic conditions at home can be divided into 7 main areas: (1) defining the basic medical issues; (2) defining the developmental issues; (3) understanding the underlying diagnoses; (4) the role of the PCP and the medical home; (5) the needs of the family; (6) the ongoing home care agencies and services required; and (7) assessment of the community and educational services.…”
Section: Insurance Coverage For Care At Homementioning
confidence: 99%
“…The findings that in Croatia the percentage of divorce in families with children with ASD is higher by about 2% than in families with healthy children, that Croatia is a post-war country with a low GDP and one of the poorest countries in Europe (Eurostat, 2009), and that the poorest dimensions of health in parents of children with ASD are energy, vitality and social functioning dimensions, indicate possible deviations from the parameters that, according to Yau and Li-Tsang (Yau& Li-Tsang, 1999), guarantee the highest quality of parenthood to a disabled child, including children with ASD. All those findings, and especially the fact that the health of parents with children with ASD compromised, are the potential threat to optimal care for child (Kelly& Hewson, 2000;Bromley& Blacher, 1991;Llewellyn et al,1999;Duvdevany& Vudinsky, 2005). All discussed facts have resulted in the finding that a great majority (71%) of parents of children with ASD believes that enhancing different political aspects would contribute to or improve their situation, quality of life and health, focusing of the social, economic and health policy, as well as streamlining the legislature, when it comes to parents of children with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Because the parents are in the centre of support for the needs of the child with intellectual disability and ASD (Turnbull et al, 2004), preserving parents' good health and well being is precondition for optimal care for child. Poor caregiver health may contribute to recurrent hospitalizations (Kelly& Hewson, 2000) and out-of-home placements for children with chronic conditions and disabilities (Bromley& Blacher, 1991;Llewellyn et al,1999;Duvdevany& Vudinsky, 2005). The therapy and rehabilitation of persons with ASD in Croatia is mostly administered in the Zagreb Autism Center, which conducted this study.…”
Section: Wwwintechopencommentioning
confidence: 99%
“…These decisions are difficult for families, and pediatricians may also be challenged when they believe that a loving family might not be the best provider of care for their own child. Llewellyn et al 20 found that parents, as a group, reported their desire to care for their child at home. Despite this finding, decisions to place a child into a congregate care setting often were made for reasons that the parents considered to be important for the "survival" of the family as a whole.…”
Section: Reasons For Placement and Decision-makingmentioning
confidence: 99%
“…The perception that professionals, such as primary care providers, expect families to care for their children at home, coupled with the lack of available support and resources, has been noted to be a source of frustration to families. 20 Hostyn and Maes 10 also found that, even with provision of "family support," many families do not feel as if all their needs are being met. Caring for children and youth with complex needs and their families requires ongoing commitment from the primary care physician and the subspecialists who may be providing the majority of the child' s medical care.…”
Section: Family Support In the Medical Homementioning
confidence: 99%